Exploring the attentional processes of expert performers and the impact of priming on motor skill execution - Adams, D. (2010)
It is widely acknowledged that under situations of heightened pressure, many expert athletes suffer from performance decrements. This phenomenon has been termed `choking under pressure` and has been the subject of extensive research in sport psychology. Despite this attention, gaps in the literature remain leaving opportunities for further advancements in knowledge about the phenomenon, particularly in relation to its underlying processes and the development of appropriate interventions that can be adopted in order to alleviate, or even prevent choking. The present programme of research, in general terms, aimed to develop and test the efficacy of an intervention tool, based on priming, to alleviate choking under pressure. It was acknowledged that such a tool should be matched to the mechanisms that underlie the choking process and although an abundance of research has provided valuable information about these mechanisms, it was identified that there still remains a lack of consensus regarding the most appropriate explanatory theory. Therefore the initial study in this thesis aimed to provide further insight into the processes that govern choking by examining accounts from elite international swimmers of their experiences of performing under high levels of pressure. The results provided further support for the postulation that choking under pressure occurs as a result of a combination of conscious processing hypothesis (Masters, 1992) and processing efficiency theory (Eysenck & Calvo, 1992) and that an optimum level of skill-focused attention is beneficial to performance. The following studies utilised this information as well as that of the existent theories of choking, to develop and examine an effective priming based intervention tool (a scrambled sentence task). Specifically, Studies 2, 3 and 4 examined the amount of residual working memory available after activation of the prime, the optimisation of the priming task and the efficacy of the tool in promoting performance under high pressure respectively. Results revealed support for the efficacy of the tool in reducing online skill-focused attention and promoting performance under both low- and high-pressure conditions. Finally, the general themes that emerged throughout the whole programme of study are discussed, as well as the limitations and recommendations for future research. Implications for coaches, athletes and practitioners are also presented.